Sosialisasi Penanganan Cedera Saat Pembelajaran PJOK Di UPT SMP Negeri 016 Nagasaribu V, Humbang Hasundutan - Julius Boy Nesra Basgimata; Sinuraya, Janwar Frihasan; Ginting, Armando Maranata; Sinuraya, Yobel Maranatha; Ginting, Adriel Yehezkiel Sumana (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
This community service activity is a comprehensive program designed to improve the capacity of teachers, students, and education personnel of UPT SMP Negeri 016 Nagasaribu V in dealing with potential injuries during PJOK learning. Through a multidisciplinary approach that combines theory and practice, this program includes three main components: (1) socialization of types of sports injuries and their mechanisms of occurrence, (2) training in first aid techniques using the PRICE method (Protection, Rest, Ice, Compression, Elevation), and (3) injury prevention workshops through correct warm-up and cool-down techniques. Implementation methods include interactive lectures, live demonstrations by a team of experts, and simulations of common sports injury cases such as ankle sprains, muscle bruises, and abrasions. Program evaluation is carried out through pre-tests and post-tests of knowledge, observations of practical skills, and distribution of guide modules that can be used as ongoing references. The expected impacts include an 80% increase in participants' understanding of injury management, the preparation of standard protocols for emergency handling of sports injuries in schools, and the creation of an injury alert team consisting of trained teachers and students. This program also produces recommendations for improving school sports facilities to minimize risk factors for injury.